2022
DOI: 10.3390/vision6010006
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Autonomic Nervous System: An Update from Anatomy to Physiological Functions

Abstract: The autonomic nervous system (ANS) confers neural control of the entire body, mainly through the sympathetic and parasympathetic nerves. Several studies have observed that the physiological functions of the eye (pupil size, lens accommodation, ocular circulation, and intraocular pressure regulation) are precisely regulated by the ANS. Almost all parts of the eye have autonomic innervation for the regulation of local homeostasis through synergy and antagonism. With the advent of new research methods, novel anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 201 publications
0
7
0
Order By: Relevance
“…A study conducted in astronauts before and after spaceflight revealed that IOP increased by 1.3 mmHg under weightlessness conditions after flight, and acute exposure to lower body negative pressure of 25 mmHg led to a decrease in IOP relative to the preflight levels [ 23 ], which highlights the influence of gravity on IOP. In addition, the sympathetic nervous system and the parasympathetic nervous system are involved in the regulation of IOP [ 24 ]. Compared with the seated position, in these postures, enhanced sympathetic nerve stimulation leads to an increased secretion of epinephrine, enhanced atrial conduction, and an accelerated heart rate [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in astronauts before and after spaceflight revealed that IOP increased by 1.3 mmHg under weightlessness conditions after flight, and acute exposure to lower body negative pressure of 25 mmHg led to a decrease in IOP relative to the preflight levels [ 23 ], which highlights the influence of gravity on IOP. In addition, the sympathetic nervous system and the parasympathetic nervous system are involved in the regulation of IOP [ 24 ]. Compared with the seated position, in these postures, enhanced sympathetic nerve stimulation leads to an increased secretion of epinephrine, enhanced atrial conduction, and an accelerated heart rate [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous humor is produced by the ciliary epithelium and drains through two independent outflow pathways: the trabecular meshwork and the uveal tract. Recently, it was reported that uveal lymphatics are also involved in IOP regulation [ 18 ]. The decrease in aqueous humor, which is related to IOP, is due to the inhibition of NO synthesis [ 19 ], and β-blockers, which have long been used to reduce IOP in glaucoma [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blood ow in the choroid is mainly regulated by the autonomic nervous system [11,13] . Therefore, choroidal thickness is more susceptible to the in uence of intraocular pressure, systemic blood pressure, and endogenous catecholamines [12,13] , and the impact of HD on choroidal and retinal thickness should differ.…”
Section: Introductionmentioning
confidence: 99%